1981
DOI: 10.1161/01.cir.64.3.586
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of diagnosis of coronary artery disease by radionuclide management of left ventricular function during rest and exercise.

Abstract: SUMMARY Rest and exercise radionuclide angiocardiographic measurements of left ventricular function were obtained in 496 patients who underwent cardiac catheterization for chest pain. Two hundred forty-eight of these patients also had an exercise treadmill test. An ejection fraction less than 50% was the abnormality of resting left ventricular function that provided the greatest diagnostic information. In patients with normal resting left ventricular function, exercise abnormalities that were optimal for diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

1982
1982
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(40 citation statements)
references
References 26 publications
1
36
0
3
Order By: Relevance
“…In fact. 21 27 Second, exercise stress may not be the appropriate provocation to elicit an abnormal coronary vasodilator response in some patients. It is possible that coadministration of a vasoconstrictor stimulus during exercise (analogous to the administration of ergonovine during pacing) might have induced left ventricular dysfunction by unmasking or exacerbating small-vessel vasoconstriction or inappropriate vasodilation.…”
Section: Radionuclide Angiographic Datamentioning
confidence: 99%
“…In fact. 21 27 Second, exercise stress may not be the appropriate provocation to elicit an abnormal coronary vasodilator response in some patients. It is possible that coadministration of a vasoconstrictor stimulus during exercise (analogous to the administration of ergonovine during pacing) might have induced left ventricular dysfunction by unmasking or exacerbating small-vessel vasoconstriction or inappropriate vasodilation.…”
Section: Radionuclide Angiographic Datamentioning
confidence: 99%
“…Indeed, previous reports about ventricular function at rest and during exercise have shown that in patients with coronary artery disease, the LVEF decreases or does not change, and regional wall motion abnormalities appear during exercise. 11,12 It is possible that such patients have residual stenosis in the infarct-related arteries and that exercise-induced ischemia is still present. In contrast, the most common response to exercise in normal volunteers is an increased LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…We presume that the fulfilment of this prerequisite for an accurate evaluation of test sensitivity and specificity25 was a major reason why radionuclide ventriculography was found to be less reliable than previously reported. Numerous reports have included patients with a history of myocardial infarction,l 1 29 These data show that the results of studies that include patients receiving beta adrenergic blockade6 11 30 are of questionable value. The relatively high sensitivity and specificity of the clinical assessment of chest pain in our study agree with those reported by others.31 32 The limited predictive power of the ST segment response to exercise is also consistent with previous findings.33 34 The increase in the left ventricular diastolic pressure with exercise has been well documented in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%